2018
DOI: 10.18203/2320-1770.ijrcog20182333
|View full text |Cite
|
Sign up to set email alerts
|

Early onset and late onset preeclampsia-maternal and perinatal outcomes in a rural teritiary health center

Abstract: Background: Preeclampsia is main cause of morbidity and mortality both mother and fetus. Preeclampsia occurs in 10-17% of pregnancies. Preeclampsia was divided into early onset preeclampsia is occur at less <34 weeks of gestation age and late onset preeclampsia is occur at >34 weeks of gestation age. Early and late onset preeclampsia have different etiology and should be considered as different disease as there are difference in clinical manifestation, maternal and perinatal outcome, prognosis and compli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 9 publications
1
1
4
Order By: Relevance
“…Of the 50 sPE participants, 34% (17/50) had EOPE. This is similar to findings of other studies: EOPE 27.6% vs LOPE 72.4% [67], and EOPE 35.5% vs LOPE 64.5% [68]. In susceptible women, EOPE occurs due to inadequate remodelling of spiral arteries while LOPE develops because the placenta overgrows its blood supply or becomes senescent.…”
Section: Discussionsupporting
confidence: 90%
“…Of the 50 sPE participants, 34% (17/50) had EOPE. This is similar to findings of other studies: EOPE 27.6% vs LOPE 72.4% [67], and EOPE 35.5% vs LOPE 64.5% [68]. In susceptible women, EOPE occurs due to inadequate remodelling of spiral arteries while LOPE develops because the placenta overgrows its blood supply or becomes senescent.…”
Section: Discussionsupporting
confidence: 90%
“…Preeclampsia has been widely considered as an independent risk factor that largely contributes to IUGR [41]. In the current research, the prevalence of IUGR (19 %) was slightly lower than the rates previously reported by some studies [42] and higher than others [43]. In 2015, Wicaksono et al, found that LOP has no effect on the incidence of IUGR (p = 0.53; PR = 1.40; 95% CI = 0.48-4.08) [44].This can be explained by the fact that in LOP there is no or slight alteration of spiral arteries diameter which results in placental hypoperfusion in some but not all cases [13].…”
Section: Discussioncontrasting
confidence: 66%
“…Our study findings are also different from Gomathy et al where 53.3% patients in EOPE and 58,6% in LOPE group were delivered by caesarean section. 16 We did not find statistically significant difference in SGA and NND between the two groups.This is in contrast with Gomathy et al where 91.6% foetuses were SGA in EOPE as compared to 54.8% in LOPE.(p0.0001). 16 Bozdag et al also found that more foetuses are SGA in EOPE group as compared to LOPE (p=0.001).…”
Section: Discussioncontrasting
confidence: 56%
“…16 We did not find statistically significant difference in SGA and NND between the two groups.This is in contrast with Gomathy et al where 91.6% foetuses were SGA in EOPE as compared to 54.8% in LOPE.(p0.0001). 16 Bozdag et al also found that more foetuses are SGA in EOPE group as compared to LOPE (p=0.001). 18 In addition, Bozdag et al found 30% neonatal deaths in preeclampsia before 34 weeks as compared to 4% afterwards (p=0.01).…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation